Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pasien Tuberkulosis Paru - Donatus Korbianus Sadipun; Winfrida Letmau (Jurnal Ilmiah Wahana Pendidikan, 2022)
Family support really supports the successful treatment of pulmonary TB patients by always reminding pulmonary TB patients to take medicine. The purpose of this study was to analyze the relationship of family support with adherence to taking medications in pulmonary tuberculosis patients. This research method is quantitative cross sectional in 40 respondents with a purposive sampling technique approach. This research was conducted on August 3-16, 2021 at Kalabahi Hospital, Alor Regency. The data collection process was carried out with 2 instruments, namely the Family Support Questionnaire and the Morinsky Medication Adherence Scale (MMAS) Compliance Questionnaire. Data analysis uses univariate and bivariate analysis where the bivariate test uses the Spearman Rank test which obtained a p value = 0.000 which is smaller than α (0.05) (meaningful). Conclusion: There is a significant relationship between family support for medication adherence of pulmonary TB patients' medications.